Impregnated With Delusion: A Case Of Pseudocyesis (Indian Journal of Case Reports, 2022)
Background- Pseudocyesis is a condition in which the patient has all signs and symptoms of pregnancy except for the confirmation of the presence of a fetus. It is the conviction of a non-pregnant woman that she is pregnant. Case presentation-Here we present a case of pseudocyesis in a forty five year old woman para 2 living 2 currently in her second marriage of fifteen years Conclusion-The management of pseudocyesis is multidisciplinary, including psychiatrists, gynecologists,and psychologists .The goal of treatment is to help patients perceive the meaning of their symptoms and to help resolve the associated stressors.